Economic and Political Determinants of Tax Amnesties in the U.S. States - Le Borgne, Eric (IMF Working Papers; Working Paper ;, 2006)
This paper revisits earlier studies on the determinants of tax amnesties. The novel findings are (i) amnesties are more likely to be declared during fiscal stress periods, and (ii) political factors significantly affect the introduction and timing of amnesties. In particular, the paper empirically disentangles opposite theoretical effects to show that governors perceive amnesties as another revenue source (rather than a tax increase alternative). Finally, supporting evidence shows that by breaking horizontal equity, amnesties might be perceived as unfair: a significant correlation exists between governors who lost their reelection bids and the introduction of a tax amnesty during their election years.